Liberty, equality, fraternity - Spicker, Paul (Policy Press, 2006)
Available Open Access under CC-BY-NC licence. Paul Spicker's new book takes the three founding principles of the French Revolution - Liberty, Equality, Fraternity - and examines how they relate to social policy today. The book considers the political and moral dimensions of a wide range of social policies, and offers a different way of thinking about each subject from the way it is usually analysed.